From new kid on the block to leading journal: a review and reflection on the first 20 years of the European Journal of Cardiovascular Nursing. (3rd January 2022) - Fredericks, Suzanne; Van Bulck, Liesbet; Ski, Chantal; Skibelund, Anne Kathrine; Sanders, Julie
Abstract: Background: This year marks the 20th birthday of the European Journal of Cardiovascular Nursing ( EJCN ). The official journal of the Association of Cardiovascular Nursing and Allied Professionals, is now recognized as one of the leading nursing and allied professional journals. Aims: This article reflects on the developments and impact of the journal over its 20-year lifespan. Methods and results: We present a descriptive account of the journal from inception (2002) until present day (2021), using data provided by the EJCN editorial office and extracted from published and available information. In the last 20 years, the EJCN has published 20 volumes, 106 issues, and 1320 papers from 79 countries. The volume and quality of papers has been consistently increasing, culminating in a 2020 impact factor of 3.908, the highest in its history, ranking second for nursing science. Papers are predominantly patient focused with a range of research methods that cover an extensive range of cardiovascular conditions. Authors who contributed to the first issue continued their contribution; 293 articles in total. Conclusion: The EJCN has evolved into a leading journal of cardiovascular care. As the journal enters its next era, with a new Editor-in-Chief, it is appropriate to have reflected on the phenomenal contribution of the outgoing Editor-in-Chief, and the editorial team, over the last 20 years.